Antibacterial Activity of Skin and Intestinal Mucus of Five Different Freshwater Fish Species Viz., Channa striatus, C. micropeltes, C. marulius, C. Punctatus and C. gachua - M., Dhanaraj; M.A, Haniffa; S.V, Arun Singh; C., Muthu Ramakrishnan; D., Manikandaraja; M., James Milton (Malaysian Journal of Science, 2009)
In the present investigation, efforts have were made to investigate out the antibacterial activity of skin mucus and intestinal mucus of five different Channa sp viz; Channa striatus, C. micropeltes, C. marulius, C. punctatus and C. gachua. The mucus collected were tested against five pathogenic bacteria namely Aeromonas hydrophila, Pseudomonas aeruginosa, Escherichia coli, Vibrio fischeri and V. anguillarum using Muller Hinton agar plates by using disc diffusion method. All the five Channa sp showed a better antibacterial activity and among the five species C. striatus showed a broad spectrum of antibacterial activity of skin mucus against A. hydrophila (19.5 ± 2mm). P. aeruginosa (28 ± 2.9mm) and V. anguillarum (24.5 ± 2.4mm) and intestinal mucus against A. hydrophila (16 ± 1.4mm), P. aeruginosa (29 ± 3.2mm), V. anguillarum (18.3 ± 1.5mm) and V. fischeri (21.5 ± 1.8). Among the five pathogens tested the maximum antibacterial activity was observed for the skin mucus against V. fischeri and the intestinal mucus against P. aeruginosa.